2007
DOI: 10.1103/physrevb.76.045332
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot energy relaxation mediated by plasmon emission in doped covalent semiconductor heterostructures

Abstract: The interaction between interface plasmons within a doped substrate and quantum dot electrons or holes has been theoretically studied in double heterostructures based on covalent semiconductors. The interface plasmon modes, the corresponding dispersion relationship, and the intraband carrier relaxation rate in quantum dots are reported. We find the critical points in the interface plasmon density of states for multilayered structures results in enhanced quantum dot intraband carrier relaxation when compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
1
17
0
2
Order By: Relevance
“…Особливо це виявляється в люмінесцентних характеристиках нанокристалів. У більшості випадків спектр фотолюмінесценції таких нанокристалів визначається лише міжзонними переходами, широко описаними в літературі [9][10][11]. Тим не менш, у спектрах люмінесценції нанокристалів халькогенідів кадмію може спостерігатися люмінесценція з участю рівнів, що асоціюються з дефектами [12].…”
Section: вступunclassified
“…Особливо це виявляється в люмінесцентних характеристиках нанокристалів. У більшості випадків спектр фотолюмінесценції таких нанокристалів визначається лише міжзонними переходами, широко описаними в літературі [9][10][11]. Тим не менш, у спектрах люмінесценції нанокристалів халькогенідів кадмію може спостерігатися люмінесценція з участю рівнів, що асоціюються з дефектами [12].…”
Section: вступunclassified
“…Many types of relaxation mechanisms were proposed to explain the experimental data evidencing that the intraband relaxation rate inside semiconductor NCs vary over a wide range from 10 8 to 10 13 s -1 . These include: (i) the two-photonassisted relaxation on optical and acoustic phonons; 21 (ii) the relaxation due to the coherent interaction of optical phonons with the electronic subsystem of the NCs; 22 (iii) the relaxation facilitated by the finiteness of the lifetime of optical phonons; 23 (iv) the relaxation mediated by the emission of plasmon and plasmon-phonon modes [24][25][26][27][28][29][30][31] residing in the regions located tens of nanometers away from the NC; (v) the relaxation due to the interaction with the NC's surface defects; [32][33][34] (vi) the multiphoton-induced relaxation, 35 (vii) Auger processes; 36 and (viii) the nonradiative energy transfer processes. 37,38 In this work, we develop a theory of pump-probe optical spectroscopy based on the pump-pulse-induced transient intraband absorption of the probe's pulse inside an anisotropic semiconductor nanorod-a quantum NC in the form of a straight circular cylinder or a rectangular parallelepiped.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of enantiomeric forms of chiral molecules is only possible through their interaction with other chiral objects [6][7][8]. Semiconductor nanocrystals, which are often intrinsically chiral because of the unavoidable surface and bulk defects, are objects of particular promise owing to their distinctive photoluminescence properties [9][10][11][12][13][14][15][16]. It has been recently demonstrated that CdSe/ZnS quantum dots and quantum rods can acquire chirality from screw dislocations naturally developing during their growth [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%